(3aJhi dGHf ceGd HGTG aj GdUhajIs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3YdeGA GdOjf GdfHhi hMceGA GdTQY GdeUWahi s
(3BNQgG (B:s
(3hefge ef HQbJ dg HhGQb GddWa aJMQc hWGH gPG eG fgJOi ef GdLhGH hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B33s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs